¿Psychosis after opioid overdose? Bilateral globus pallidus ischaemic injury as an unsuspected organic cause. - Vélez-Leal, Juan Luis (2022)
The approach to intoxicated patients with a previous history of psychopathological manifestations represents a challenge to medical care. The presence of a dual pathology can lead to somatic symptoms being dismissed and not considered as possible manifestations of a serious underlying pathology. We report the case of a patient who, during her hospitalization for a depressive episode, presented an incidental opioid overdose. Upon recovery, she presented disorganized behavior and delusions, initially attributed to her depression. Further studies demonstrated, however, a serious underlying organic cause: A bilateral ischaemic injury of the globus pallidus. The clinical picture is analyzed in the light of the relevant literature, addressing the issues of delirium, clinical spectrum of globus pallidus lesions and ending with a brief description of opioid overdoses and neurotoxicity. Faced with symptoms that are not consistent with the usual course of a psychopathological decompensation or drug intoxication, possible organic causes should be delved into. It is suggested that neuroimaging studies be considered in any patient who suffers from an opioid overdose and who later presents severe cognitive alterations.